Determinação de sinvastatina em plasma humano por cromatografia líquida de ultra performance acoplada a espectrometria de massas (UPLC-MS/MS) para aplicação em estudos farmacocinéticos de bioequivalência - Silva, Suéllen Cristina Rennó (2012)
Simvastatin (member of the statin class) is an antilipemic agent used in the primary treatment of primary hypercholesterolemia. The simvastatin reference drug in Brazil is Zocor® (Merck Sharp & Dohme Pharmaceutical Ltda.). The generic and similars drugs can be considered as “copies” of the reference drug. Relative bioavailability studies and pharmaceutical equivalence studies are needed before submitting the registration petition of these drugs. Thus, the aim of this work was the development and validation of a bioanalytical method for application in relative bioavailability studies in healthy volunteers. Liquid-liquid extraction was employed as a purification technique and the ultra performance liquid chromatography/tandem mass spectrometry (UPLC-MS/MS) as a quantitative technique. The method was developed and validated and presented a linear range of 0.4 – 40.0 ng/mL, and fulfilled all preset criteria for selectivity, recovery, precision, accuracy and stabilities according to ANVISA`s RE 899/2003 and FDA`s Bioanalylical Method Validation Guidance. After the validation, the method was applied to the relative bioavailability study of simvastatin. The pharmacokinetics parameters results was obtained through the blood concentration-time curves, and statistically analyzed for the determination of bioequivalence. The following pharmacokinetic parameters were obtained: AUC, Cmax, tmax. The developed method showed simple sample preparation, low lower limit of quantification and short running time, which was suitable for applying. Therefore, the proposed bioanalytical method and the bioequivalence study showed adequate for evaluating the simvastatin 40 mg tablet formulations (reference and test). The test drug analyzed was not considered bioequivalent to the reference drug.